Lack of response to garlic fed at different dose rates for the control of Haemonchus contortus in Merino wether lambs - Strickland, V.; Fisher, James; Potts, W.; Hepworth, G. (CSIRO Publishing, 2009)
With the increased incidence of parasite resistance to chemical anthelmintics worldwide novel approaches to manage parasite infection, such as medicinal plants and their extracts, are being investigated by the scientific community. The current study tested the effect of three rates of garlic (0.9, 1.8 and 3.6%) in a pelleted ration on Haemonchus contortus in sheep. Thirty-nine Merino wether lambs aged 6 months were divided into five treatment groups, including three garlic dose rates and two control groups that received no garlic. All animals were infected with 4000 L3 H. contortus larvae 3 weeks after allocation to treatments. A positive control group was drenched with abamectin 28 days after infection. The synthetic drench was effective in controlling the parasites, but there was no reduction in either worm egg counts (WEC) or total worm count due to the garlic. The 3.6% garlic treatment had significantly lower (P <0.05) liveweight, feed intake, body condition score and feed conversion ratio than any of the other treatment groups, suggesting that this level of garlic had a low level of anti-nutritional properties. There was an interaction between faecal WEC and voluntary feed intake overtime, with the animals with higher voluntary feed intake having lower WEC over time.